Identification of Active Antioxidant Compounds from Ungu Leaf Ethanol Extract (Graptophyllum pictum L. Griff) - Rustini, Ni Luh (Journal of Health Sciences and Medicine; Vol 2 No 1 (2018): JHSM (February 2018), 2018)
This study was conducted to determine the chemical compounds contained in ungu leaf ethanol extract that has antioxidant properties. Ungu leaf powder (2000 g) was extracted with 10,000 mL of 96% ethanol yielding 51.77 g thick purple-green viscous extract. The result of phytochemical test on ungu leaf ethanol extract showed that the extract contained flavonoid, saponin, phenolic and steroid, with the highest content being steroid. The separation of the ethanol extract was carried out by column chromatography using silica gel as a stationary phase and a mixture of n-hexane: dichloromethane: ethyl acetate (2: 1: 1) as the mobile phase, yielding 10 fraction groups. Fraction F1 is relatively pure, then identified with UV-Vis, IR, and GCMS spectrophotometers. The results of identification with UV-Vis, IR, and GC-MS spectrophotometers showed that ungu leaf ethanol extract containing antioxidant activity contained stigmasterol compounds, namely: stigmasta-5,22-dien-3-ol and stigmast acid-5-en-3-ol.